The Impact of Aerobic Dance Intervention on Postural Balance in Children: A Randomized Controlled Trial - Ghada Jouira; Cristina Ioana Alexe; Khawla Zinelabidine; Haithem Rebai; George Danuț Mocanu; Adin Marian Cojocaru; Luciana Dragomir; Denis Čaušević; Sonia Sahli (MDPI AG, 2024)
This study aimed to investigate the impact of an 8-week aerobic dance intervention on postural balance in children. Forty-one children, aged 9 to 11, were randomly assigned to either an aerobic dance group (ADG) or a control group (CG) from a primary school. Postural balance was assessed using center of pressure (CoP) excursions before and after the 8-week intervention period. Evaluations were conducted on both firm and foam surfaces in bipedal and unipedal stances under open-eyes (OE) and closed-eyes (CE) conditions, as well as on both medial-lateral (ML) and anterior-posterior (AP) surfaces in a bipedal stance under OE conditions. The ADG exhibited significantly decreased CoPVm values during firm bipedal CE, unipedal OE, foam bipedal OE and CE, and foam unipedal OE (p < 0.005). This study suggests that aerobic dance intervention improved postural balance in children, showcasing adaptability and improved stability under various conditions.